Utilizing Mobile Assisted Language Learning (MALL) for Teaching English to Non- Formal Learners in Pakistan - Muhamamd Mooneeb Ali; Zoobia Asad; Shagufta Moghal (Journal of Arts & Social Sciences, 2020)
Non formal education is an important education type that helps the availability and continuity of education where formal schooling is not available. English language learning assumes a significant role in the National Educational program. Despite its importance, English Language learning is a problematic area for learners in the formal and non-formal education systems. This research intends to explore the importance of using mobile assisted language learning (MALL) in non-formal English language environments in Pakistan. The population of this research comes from various institutions all over Punjab, Pakistan, where 60 non - formal learners were chosen through simple random sampling method. The research design was experimental whereas test (pre and post) was used as a tool to collect data. The findings present that MALL created a significant impact on English Language learning of non-formal learners. It further ascertained that MALL can be an attractive and result oriented method in non-formal settings.